Justification of Sentencing Decisions: Development of a Ratio-Based Measure Tested on Child Neglect Cases - Watamura, Eiichiro; Ioku, Tomohiro; Wakebe, Toshihiro (Frontiers in Psychology, 2022)
Theoretically, people’s justification of a sentencing decision involves a hybrid structure comprising retribution, incapacitation, general deterrence, and rehabilitation. In this study, a new ratio-type measure was developed to assess this structure and was tested to detect changes in the weighting of justification according to the content emphasized in a particular crime. Two child neglect scenarios were presented to participants, where they read either a severe-damage scenario (where a single mother’s selfish neglect caused her son’s death) or a moderate-damage scenario (where a single mother became apathetic due to economic deprivation and caused her child’s debilitation). Participants then indicated the proportion of importance they placed on each justification in determining the defendant’s punishment, with an overall proportion of 100%, along with responding to the sentence on an 11-point scale. This study involved a two-factor analysis of variance for justification ratios, a t-test for the sentence, and a multiple regression analysis with three demographic variables, the four justifications as independent variables, and the sentence as the dependent variable. The ratio of retribution to rehabilitation was reversed depending on the scenario: in the severe-damage scenario, retribution was weighted highest at 27.0% and rehabilitation was weighted at only 19.0%. By contrast, in the moderate-damage scenario, rehabilitation had the highest weighting of about 26.2%, while retribution was weighted at 21.5%. The sentence was more severe in the severe-damage scenario. Multiple regression analysis suggested that in the severe-damage scenario, most participants failed to deviate from choosing retribution by default and decided on heavier sentences, while some who considered rehabilitation and incapacitation opted for lighter sentences. The present measure succeeded in detecting changes in the weighting of justification, which can be difficult to detect with common Likert Scales. In addition, it was found that not only retribution but utilitarian justification was considered in the sentencing decisions of serious cases.